Hierarchical control of microgrid with distributed generation and distributed energy storage system - Yu, Jiale (2017)
Nowadays, there has been more and more extensive research on dc microgrid system and its applications. To ensure an excellent performance of the system, two aspects are always concerned: choice of distributed generation units and energy storage units; and means of power electronic converter control and hence the design of controller. In this project, the main objective is to improve the design of the hierarchical control structure and control algorithm of dc microgrid. Firstly, a comparison is done in depth between dc microgrid and ac microgrid to illustrate the advantages of a dc system, followed by a number of circuit structures that are illustrated in detail, experimented and evaluated. Then with extensive research and comparison of existing control techniques, a hierarchical control design is chosen and applied to the dc microgrid system, and tested on its feasibility and reliability for practical application.